A Study of Student Contribution Towards Developing New Approach of Sustainable Campus in UTHM Pagoh Campus - Adzmi, Aizat Hamsyari; Abdul Zaki Bin Abdul Wahid (Progress in Engineering Application and Technology, 2022)
This study shows the results about the study of student’s contribution towards under developing of sustainable campus on UTHM Pagoh Campus. As we all know, UTHM Pagoh Campus is currently under the progress slowly toward sustainable campus. Therefore, in this research we want to identify level of student’s involvement and interest towards initiated sustainable programmes. But, before that, research about the current and planned initiated sustainable program that can be initiate must find out first. This is to increase more knowledge about a sustainable building in a campus. Other than that, the objective of the study is to identify initiated sustainable program towards green campus in UTHM Pagoh, to identify the level satisfaction of students on the current progress toward sustainable building and to analyse the level of students’ involvement and contribution towards initiated sustainable programs. In this research, to determine the pattern of the situation, quantitative approaches were used. The data collected from respondents were analysed using SPSS, Microsoft Excel, and Google Forms. This research also gives a proper recommendation based on data that have been collect and making analysis on the questionnaire that have been distributes. To conclude, the awareness level among students is moderate, and the result can be used for future research to ensure the level of students’ awareness can be increased for the environmental aspect and can prevent from pollution and land destruction.